Clinical profile of ischemic stroke and its correlation with serum uric acid: a cross sectional study - Lakhmawad, Hemant; Humaney, Nalini (International Journal of Advances in Medicine, 2020)
Background: Stroke is the third most common cause of mortality if considered separately from other cardiovascular diseases across the world. Uric acid also has neuro protective effect and has been postulated in increased risk of insulin resistance and cardiovascular risk. With this background, conducted a study to understand the clinical profile of ischemic stroke and its correlation with serum uric acid in setup. Materials and Methods: A cross sectional study was carried out in a tertiary care hospital from October 2016 to September 2018. A total of 75 patients with history of acute stroke were included in the study after obtaining informed consent. Clinical data including demographic data, age and sex of the patients was taken. Also, history of diseases like diabetes mellitus, hypertension and Ischemic Heart Disease was noted. Relevant investigations were done and noted. Results: The mean age of the study subjects was 57.53 ± 10.23 years with male preponderance. The mean body mass index was 26.58 ± 2.86 in our study. Risk factors like hypertension were present in 70.67%, TIA was present in 6.67%, 22.67% had diabetes mellitus and smoking was present in 48% of the patients. About 54.67% of the subjects had high uric acid levels in our study. Not found any significant relation between the uric acid levels and different risk factors. Conclusion: The average age of the ischemic stroke incidence was between 5th to 6th decades in the present study. Males had higher risk when compared females which were consistent with various studies conducted across the world. Not found any significant association between the uric acid levels and various risk factors for ischemic stroke. Uric acid was found to higher among these patients.